Translation and Transcreation: Scottish Perspectives. (3rd July 2019) - Hubbard, Tom
ABSTRACT: The role of both Scots and English as target languages for translation is discussed, together with consideration of the contrasting concepts of utilitarian 'translation' and literary 'transcreation'. Aesthetic, linguistic and cultural challenges to the 'transcreation' process are set forth, followed by examples of the influence of one culture upon another.